2016
DOI: 10.11646/zootaxa.4193.2.13
|View full text |Cite
|
Sign up to set email alerts
|

New records and species of Crepidodera Chevrolat (Coleoptera: Chrysomelidae) in Eocene European amber, with a brief review of described fossil beetles from Bitterfeld amber

Abstract: Based on six relatively well-preserved specimens from Eocene Baltic amber, Crepidodera tertiotertiaria sp. nov. is described. The new species is illustrated and compared with morphologically similar extant and fossil relatives. It is the third described fossil species of Crepidodera Chevrolat. In addition to the new taxon, new fossil records of C. decolorata Nadein & Perkovsky from Baltic and Bitterfeld amber are presented. A key to species of Crepidodera described from fossil resins is provided, and a checkli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 479 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…A. gedanicola is similar to A. fuscipes (Gyllenhal, 1808). A. groehni is similar to A. pusilla (Paykull, 1798) and A. morio Kolenati, 1846. Silken fungus beetles from other Late Eocene ambers are less studied: from Rovno amber were described three cryptophagine species [Lyubarsky, Perkovsky, 2010, 2011, 2012, from other faunas no species were named [Bukejs et al, 2016]. In the present paper we describe a new species of Atomaria from Bitterfeld amber.…”
Section: Introductionmentioning
confidence: 82%
“…A. gedanicola is similar to A. fuscipes (Gyllenhal, 1808). A. groehni is similar to A. pusilla (Paykull, 1798) and A. morio Kolenati, 1846. Silken fungus beetles from other Late Eocene ambers are less studied: from Rovno amber were described three cryptophagine species [Lyubarsky, Perkovsky, 2010, 2011, 2012, from other faunas no species were named [Bukejs et al, 2016]. In the present paper we describe a new species of Atomaria from Bitterfeld amber.…”
Section: Introductionmentioning
confidence: 82%
“…Unfortunately, there are no comprehensive published summaries of the number of endemic Bitterfeld insect species for comparison, but in contrast to the similarities observed by some authors, Alekseev and Grzymala (2015) described nine tenebrionid beetles from Baltic and Bitterfeld amber but did not find any shared species between both deposits. Bukejs et al (2016) provided a checklist of beetle species described from Bitterfeld amber and found some species to be shared, although other species (and genera) are unique to Bitterfeld (Lyubarsky and Perovsky 2017). In summary, most palaeoentomological studies suggested at strong similarities between Baltic and Bitterfeld ambers, but also noted that taxonomic knowledge is still very fragmentary.…”
Section: Discussionmentioning
confidence: 98%
“…exposed distal parts of male and female genitalia in Aderidae (Alekseev and Grzymala, 2015), Anthicidae , Cantharidae (Kazantsev, 2013), Chrysomelidae (Bukejs and Chamorro, 2015;Bukejs et al, , 2016, Cupedidae (Kirejtshuk, 2005), Ischaliidae (Alekseev and Bukejs, 2017), Lycidae (Kazantsev, 2019), Melandryidae (Alekseev, 2014), Pyrochroidae (Bukejs et al, 2019), Scirtidae (Heuss, 2008;Klausnitzer, 2012), Staphylinidae (Jałoszyński et al, 2018;Brunke et al, 2019;Shavrin and Yamamoto, 2019), Tenebrionidae (Nabozhenko et al, 2019a, b;Alekseev et al, 2020a), Zopheridae (Alekseev and Bukejs, 2016) and other groups.…”
Section: Discussionmentioning
confidence: 99%
“…Although most estimates of the age of Baltic amber have suggested that it is derived from the early part of the middle Eocene (Lutetian, 47.8-41.2 Ma) based largely on K-Ar dating (Ritzkowski, 1997), palynological biostratigraphy of the specific region where the sample originated suggests a younger, late Eocene (Priabonian, 37.8-33.9 Ma) age (Aleksandrova and Zaporozhets, 2008). An intermediate, middle Eocene (mostly Bartonian, age was recently proposed for the extinct central European resinproducing forests according to the stratigraphy of the Sambian amber deposits (Bukejs et al, 2019). Following classical views (e.g.…”
Section: Introductionmentioning
confidence: 99%